2013
DOI: 10.1007/s00190-013-0638-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping GPS positional errors using spatial linear mixed models

Abstract: Nowadays, GPS receivers are very reliable because of their good accuracy and precision; however, uncertainty is also inherent in geospatial data. Quality of GPS measurements can be influenced by atmospheric disturbances, multipathing, synchronization of clocks, satellite geometry, geographical features of the observed region, low broadcasting coverage, inadequate transmitting formats, or human or instrumental unknown errors. Assuming that the scenario and technical conditions that can influence the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…(IV) Measuring the emission rate of an aerosol also faces with measurement error which studied by Bémer et al (2002). (V)Finally, the altitude as a GPS information faces with measurement error as well, which discussed in previously mentioned study Militino et al (2013).…”
Section: Piemonte Datasetmentioning
confidence: 93%
“…(IV) Measuring the emission rate of an aerosol also faces with measurement error which studied by Bémer et al (2002). (V)Finally, the altitude as a GPS information faces with measurement error as well, which discussed in previously mentioned study Militino et al (2013).…”
Section: Piemonte Datasetmentioning
confidence: 93%
“…Le‐Gallo and Fingleton () considered the case of cross‐sectional spatial regression models with MEs in the explanatory variables and demonstrated that ME in an independent variable is one reason why ordinary least squares estimates may not be consistent. Militino, Ugarte, Iribas, and Lizarraga‐Garcia () addressed the quality of the Global Positioning System measurements using a likelihood‐based approach for the analysis of positional errors based on a spatial linear mixed model. In line with the observations in the work of Li et al (), Huque, Bondell, and Ryan () showed that the presence of covariate MEs can lead to significant sensitivity of parameter estimation to the choice of the spatial correlation structure.…”
Section: Introductionmentioning
confidence: 99%
“…Kriging (see e.g., [10]), though originating in the field of mining, is developed to fully account for spatio-temporal information on data [10]. Since then, it has become a powerful tool in geostatistics and spatial statistics to handle spatially and/or temporally correlated and irregularly distributed data and has been widely applied to other fields such as hydrology [11], climatology [12], soil science [13], ecology [14], Geo-Information System (GIS) [15], atmosphere science [16], geophysics [17] and geodesy [18]. Since 2002, it has been shown to be efficient for ionospheric delay estimation as well.…”
Section: Introductionmentioning
confidence: 99%